2005
DOI: 10.1080/10739680590934736
|View full text |Cite
|
Sign up to set email alerts
|

Differential Coronary Microvascular Exchange Responses to Adenosine: Roles of Receptor and Microvessel Subtypes

Abstract: Objective-To assess the role of adenosine receptors in the regulation of coronary microvascular permeability to porcine serum albumin ( ).Methods-Solute flux was measured in single perfused arterioles and venules isolated from pig hearts using fluorescent dye-labeled probes by microspectro-fluorometry. Messenger RNA, protein, and cellular distribution of adenosine receptors in arterioles and venules were analyzed by RT-PCR, immunoblot, and immunofluorescence.Results-Control venule (10.7 ± 4.8 × 10 −7 cm s −1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 71 publications
3
28
1
Order By: Relevance
“…The first result, contrary to expectation (43), was that basal permeability of venules was not higher than that of the arterioles. Indeed, this outcome is in contrast with that observed in other vascular beds (venular P s Ͼ arteriolar P s ) including adult (29,57) and juvenile porcine heart (24, 59) and skeletal muscles of adult male rat (48), mouse (48), guinea pig (43), and rabbit (50). The primary difference between the current study and those published previously is that the venous values are significantly lower than reported for other rodent skeletal muscle models (adult male) (57).…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…The first result, contrary to expectation (43), was that basal permeability of venules was not higher than that of the arterioles. Indeed, this outcome is in contrast with that observed in other vascular beds (venular P s Ͼ arteriolar P s ) including adult (29,57) and juvenile porcine heart (24, 59) and skeletal muscles of adult male rat (48), mouse (48), guinea pig (43), and rabbit (50). The primary difference between the current study and those published previously is that the venous values are significantly lower than reported for other rodent skeletal muscle models (adult male) (57).…”
Section: Discussioncontrasting
confidence: 46%
“…9), consistent with the proposal that microvessel barrier resistance by ADO was primarily mediated by the ADO A 2A receptor-adenylyl cyclase pathway. We also found that ADO A 2A receptors exist in arteriolar smooth muscle cells (57 ). Others have shown that A 2A receptors are expressed on platelets, neutrophils, and mast cells, all of which they are involved in anti-inflammatory activity, especially under ischemic conditions (35).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations